2006
DOI: 10.3844/ajessp.2006.27.32
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Chromium Sorption on Biomass Fungi from Aqueous Solution

Abstract: Abstract:The kinetics of chromium ions sorption from aqueous solution on fungi biomass have been investigated in a batch system. The experimental data were analysed based on an intraparticle diffusion equation and a pseudo-second-order mechanism, in order to predict the constant rate of sorption and the equilibrium capacity with the effect of initial chromium ions concentration, temperature and initial solution pH. The results indicate that the sorption mechanism is described by a pseudo-second order equation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
0
17
0
6
Order By: Relevance
“…Among many kinetics models reported, the intraparticle diffusion model is helpful in understanding the kinetics of interaction of heavy metals and adsorbents at microscopic level [15,16]. In this research, time dependence of the extent of sorption of Cr(VI) was used as a measure of the rate of interaction of Cr(VI) with brick clay particles, fired at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many kinetics models reported, the intraparticle diffusion model is helpful in understanding the kinetics of interaction of heavy metals and adsorbents at microscopic level [15,16]. In this research, time dependence of the extent of sorption of Cr(VI) was used as a measure of the rate of interaction of Cr(VI) with brick clay particles, fired at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural and synthetic sorbents, such as fungi, rice husk, maize cob, fruit waste and different types of clay are used to remove heavy metals from effluents [9][10][11][12][13][14][15]. Equilibrium and kinetics studies of sorption of many heavy metals on these adsorbents have already been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the steric effect exerted by the methyl group substituents on positive nitrogen active site. To examine the rate determining step of the adsorption reaction, the uptake time data obtained were treated according to the equation [31] q t = x + k i t 0.5 (5) where k i (mmol/g min 0.5 ) is the intraparticle diffusion rate constant and x is indication for the thickness of the boundary layer. The straight line obtained and the positive values of x ( Fig.…”
Section: Kineticsmentioning
confidence: 99%
“…The relationship between the uptake and the square root of time indicates the effect of the intraparticle diffusion on the rate of reaction. The rate of intraparticle diffusion can be described as [38]:…”
Section: Kinetic Studiesmentioning
confidence: 99%